IMPLEMENTASI MAQASID SYARIAH DALAM TRANSAKSI MURABAHAH PADA ENTITAS SYARIAH - Jannah, Miftahul (JURNAL ILMIAH EDUNOMIKA, 2023)
The research aims to analyze the application of maqasid Sharia in murabahah transactions in Islamic entities. This research is a study that applies a qualitative research approach. By using secondary data sources, namely international journals consisting of 9 journals as references. The results of the analysis show that the application of maqasid Sharia as daruriyat (necessity) financial statements in murabahah transactions which there are five basic elements, these elements are the spirit of Sharia because Islam suppresses and spreads them to protect them from people who ignore them. While the complementary (hajjiyat) and jewelry (tahsiniyat) is a complement to the basic needs used to eliminate difficulties or obstacles in every financial transaction.